The Effectiveness of the Problem-Based Learning Model Assisted by Augmented Reality on Learning Outcomes in the Material of the Forms of the Five Senses and Their Functions - Fajar Aunurofiq; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The low learning outcomes of students are caused by the inconsistency of the learning model and media with Permendikbudristek Number 16 of 2022 concerning Process Standards. This study aims to test the effectiveness of the Problem-Based Learning (PBL) model assisted by Augmented Reality (AR) compared to the PBL (teacher version) model assisted by image media on the learning outcomes of grade IV science students of SD Gugus Lokantara, Temanggung District, Temanggung Regency. This type of research is an experiment with a quasi-experimental research design in the form of a Non-Equivalent Control Group Design. Data collection techniques were in the form of test techniques (pretest and posttest); non-test techniques in the form of observation, interviews, questionnaires, and documentation. Data analysis techniques include initial data analysis with normality test and homogeneity test and final data analysis with t-test and N-Gain test. From the t-test results obtained sig. value of 0.002 (<0.05) so that H0 is rejected and Ha is accepted. The output of the N-Gain test of the experimental class is 0.68 and the control class is 0.50. In conclusion, the PBL model assisted by AR is effective and has a higher average increase in learning outcomes compared to the PBL model (teacher version) assisted by image media in science learning for grade IV SD Gugus Lokantara, Temanggung District, Temanggung Regency.